COMPUTED TOMOGRAPHIC FINDINGS IN 15 DOGS WITH EOSINOPHILIC BRONCHOPNEUMOPATHY. Issue 1 (15th August 2014) - Mesquita, Luis; Lam, Richard; Lamb, Christopher R.; McConnell, J. Fraser
<x xml:space="preserve">Abstract</x> Eosinophilic bronchopneumopathy is a disease characterized by the infiltration of the lung and bronchial mucosa by eosinophils. The aim of the present study was to describe the CT findings in a large series of dogs with confirmed diagnosis of eosinophilic bronchopneumopathy. Computed tomographic scans of 15 dogs with confirmed diagnosis of eosinophilic bronchopneumopathy were evaluated retrospectively by two boarded radiologists who reached a consensus. Abnormalities were identified in 14/15 (93%) dogs, including pulmonary parenchymal abnormalities in 14/15 (93%) dogs, bronchial wall thickening in 13 (87%) dogs, which was considered marked in eight (53%), plugging of the bronchial lumen by mucus/debris in 11 (73%) dogs, and bronchiectasis in nine (60%) dogs. Pulmonary nodules were identified in 5/15 (33%) dogs including one dog with a mass. All dogs with a nodular lung pattern had additional abnormalities. Lymphadenopathy was present in 10 dogs (67%). Lesions associated with eosinophilic bronchopneumopathy are variable and heterogeneous and encompass a wider variety of computed tomographic features than reported previously. Computed tomographic images were abnormal in the majority of affected dogs, hence CT is a useful modality to characterize the nature and distribution of thoracic lesions in dogs with eosinophilic bronchopneumopathy.